TEKNOLOGI PEMBUATAN BAHAN BANGUNAN BERBAHANPASIR (BATAKO) HASIL ERUPSI MERAPIDI LERENG BAGIAN UTARA - Darmono, - (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
The program of the production technology application of the sandbasedbuilding material aims to equip the community of Desa Kalibeing,Kecamatan Dukun, Central Java with: (1) life skill of vocational skill insand-based building material production, (2) enterpreneurship interest inbuilding material production, and (3) capability to develop sand-basedbuilding material production industry.The technology application method consists of the activities: (1)survey of the skill types interested by the target community, (2) talk of lifeskill education related to sand-based building material production, (3)discussion, (3) demonstration, (4) practice of concrete block production, and(5) laboratory test to observe the product quality and analysis of the trainingproduct economic value. The talk and discussion methods are used todeliver the raw material preparation subject, the demonstration and practicemethods are used to equip the community the skill in concrete blockproduction, and the laboratory research aims to observe the quality andeconomic value of the products. The target community of the technologyapplication is the community of Desa Kalibening, Kecamatan Dukun,Central Java. The activity result is analysed by observing the level of thecapability of the training participants in producing sand-based buildingmaterial especially concrete blocks and the quality of the training resultproducts if compared to the existing standards and the selling value of theproducts.The result of the technology application implementation of the sandbasedbuilding material production is the community mastering the skills of:(1) good preparation of raw material to form the concrete blocks, (2)capability of producing sand-based building material especially the concreteblocks with various mixing ratios, (3) treatment of the produced buildingmaterial, and (4) enterpreneurship capability of producing sand-basedbuilding materials especially concrete blocks. Generally the buildingmaterial products made by the target community have met the requirementsset in SNI although they are still in the lowest quality category (A1). Theselling value of the concrete blocks with the ratio of 1 SP : 10 PS is Rp2.000,00 each and the ratio of 1 SP : 12 PS is Rp 1.800,00 each.